2015
DOI: 10.4103/0974-8237.156062
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia secondary to basilar impression: A case report

Abstract: We report a rare case of trigeminal neuralgia. A 23-year-old woman with a history of 1 year of typical trigeminal neuralgia manifested the characteristics of basilar impression. Magnetic resonance imaging (MRI) demonstrated basilar impression, deformity of the posterior fossa with asymmetry of petrous bone, and compression of medulla oblongata in the topography of the odontoid apophysis. The operation was performed through a suboccipital craniectomy. The neuralgia disappeared after surgery and remains complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The most common cause of TN is compression of the fifth cranial nerve at its REZ by a vascular loop [ 1 ]. Although the role of anatomical structures in the pathogenesis of TN has not been well understood, previous studies suggested a relationship between susceptibility to TN and canonical structural anomalies, such as cases of TN associated with posterior cranial deformities [ 6 , 7 ], among which Smartt et al reported that the petrous ridge angle was larger in the lambdoid synostosis group on the unaffected side [ 8 ]. In the present case, the following anatomical parameters were observed: the length of the TGN was shorter on the unaffected side (8.1 mm vs. 9.2 mm); the calculated area of the cistern was narrower (170.2 mm 2 vs. 198.0 mm 2 ) on the unaffected side at the level of the fifth cranial nerve; and the angle between the ventral median line and the petrous ridge (petrous ridge angle) was larger on the unaffected side (131° vs. 122°), although deviation of the median line of the patient’s skull impeded correct assessment of the actual petrous angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause of TN is compression of the fifth cranial nerve at its REZ by a vascular loop [ 1 ]. Although the role of anatomical structures in the pathogenesis of TN has not been well understood, previous studies suggested a relationship between susceptibility to TN and canonical structural anomalies, such as cases of TN associated with posterior cranial deformities [ 6 , 7 ], among which Smartt et al reported that the petrous ridge angle was larger in the lambdoid synostosis group on the unaffected side [ 8 ]. In the present case, the following anatomical parameters were observed: the length of the TGN was shorter on the unaffected side (8.1 mm vs. 9.2 mm); the calculated area of the cistern was narrower (170.2 mm 2 vs. 198.0 mm 2 ) on the unaffected side at the level of the fifth cranial nerve; and the angle between the ventral median line and the petrous ridge (petrous ridge angle) was larger on the unaffected side (131° vs. 122°), although deviation of the median line of the patient’s skull impeded correct assessment of the actual petrous angle.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are scattered reports of NVC-related TN in adult patients associated with diseases involving posterior cranial deformities [ 6 , 7 ]. Based on these considerations, mild lambdoid synostosis cases, especially adults who were asymptomatic in childhood, may experience more frequent TN due to NVC associated with deformities of the posterior cranial fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the theory of peripheral lesions has been accepted by most scholars (13). Regarding the pathogenesis of TN, it is believed that the trigeminal nerve becomes chronically compressed by abnormal twisted microvessels in the REZ area, resulting in inflammation and demyelination changes in the root of the trigeminal nerve and thus in a "short circuit" of membrane potential and neuropathic pain in the trigeminal nerve distribution area (14). One study (4) showed that the size, shape, and structure of the skull varies according to race and sex.…”
Section: Discussionmentioning
confidence: 99%
“…The space occupied by tissues of the posterior fossa is small, resulting in NVC of the trigeminal nerve and clinical symptoms. However, for people with a large posterior fossa volume, there will be no symptoms of compression, clinical pain or other discomfort, even if the blood vessels are in contact with the nerve ( 15 ). In our study, the mean VPCF in the UTN group was significantly lower than that in the healthy control group ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Bony abnormalities, as petrous bone deformities or basilar impression, causing compression over trigeminal nerve or nucleus have been reported previously [ [8] , [9] , [10] ]. However, EST as a cause of TN has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%